The Comparative Suitability of Different Solvents Used in the Fractionation of Methanol Leaf Extract of Persea americana Mill: An in Vitro Studies - Yakubu, Ojochenemi E.; Otitoju, Olawale; Danjuma, Janya; Maianguwa, dulrashid Dauda; Umaru, Isaac John; Oladele, Gloria Omonefe (African Journal of Biochemistry and Molecular Biology Research, 2024)
This research investigated the suitability of various solvents used in the fractionation of methanol leaf extract of P. americana to ascertain the flavonoid, vitamin and amino acid profile of the fractions. It has been demonstrated that a number of Persea americana plant components contain different phytochemicals associated with important biological function. Fresh leaves of P. americana were harvested from Baissa in Taraba State. The plant materials were air dried under shade at ambient temperature. The dried plant materials were pulverized to fine powder using mortar and pestle. The pulverized plant material was soaked in methanol for 72 hours for extraction. The extract was filtered using clean filter cloth and filter paper under reduced pressure. The filtrate was evaporated in in rotary evaporator and water bath to obtain the required concentrate. The extract was used to perform fractionation using separation funnel and solvents of different polarity such n-hexane, methanol and ethanol. Each of the fractions was used to analyze for flavonoid, vitamin and amino acid profile using HPLC. The result reveals that quercetin is present in each of the fractions. Caffeic acid phenyl ether was detected in diluted ethanol fraction, coumaric acid was identified in diluted n-hexane fraction, caffeic acid was identified in methanol fraction chlorogenic acid detected in n-hexane fraction. Vitamin K was identified in all the fractions, Vitamin B1 was identified in diluted ethanol fraction and n-hexane fraction while vitamin B9 was detected in diluted n-hexane fraction and n-hexane fraction. Vitamins B2 and B6 were identified in methanol fraction and diluted ethanol fraction respectively. The diluted ethanol fraction was seen to contain 8 different amino acids followed by the methanol fraction with 6, then the diluted n-hexane fraction with 3 and the n-hexane fraction with 2. This reveals that for isolation of amino acids, the ethanol fraction may be more suitable considering that the highest number of amino acids were found in it.